(3UahI eG GfJTQ ef CNHGQ UdMGA GdbQf GdMGOi YTQs - (3CHh YHjO Gddg SjO eMeO GdUZjQs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hSejJ cJGHi gPG UahI eG GfJTQ ef CNHGQ UdMGA GdbQf GdMGOi YTQ LeYI ef YOI cJH Jfja Yf YTQjf cJGHkG Je jHOC HJQLeI (B: (3CHh eMeO SjOi YHO Gddg Hf Ydi Hf WGgQ GdTQja GdMSfi GdeSLdeGSi hEfeG HOCJ Hg eY chfg eGJ hSW GdbQf s
(3BNQgG (B:s
(3fGbU hjfJgi BNQ GdehLhO efg HJQLeI CHh YHO Gddg ehdGfG eMeO Hf GdEeGe GdTgjQ ehdGfG YHO Gddg Hf Ydi Hf WGgQ GdMSfi hjYQa HSLdeGSI HehdGi GHf Ydi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eLOhdI HGdMHQ GdCMeQ heYfhfI HGdMHQ GdCMeQ hGdCRQGb s
(3hgj ebGHdI s
(3hGdhQbI bHd GdCNjQI efgG ebWYI hVGY CcKQ ef fUagG HjfeG GdhQbI GdCNjQI egdgdI CjVkG hVGYJ eYXe cdeGJgG s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs